Analysis Of Working Capital Management Performance In Malaysian Consumer Product Companies - Abdul Nasser, Abu Thahir (2007)
The purpose of this study is to examine the relationship between the size of the firm and its performance in working capital management. Working capital manaagement plays a vital role to enhance the economic performance of the corporate sector. This study also established evidence that the performance in working capital management is significantly affected by the profitability and current assests of the firms.